2012
DOI: 10.1177/0963662512440913
|View full text |Cite
|
Sign up to set email alerts
|

How the public engages with global warming: A social representations approach

Abstract: The present study utilises social representations theory to explore common sense conceptualisations of global warming risk using an in-depth, qualitative methodology. Fifty-six members of a British, London-based 2008 public were initially asked to draw or write four spontaneous "first thoughts or feelings" about global warming. These were then explored via an open-ended, exploratory interview. The analysis revealed that first thoughts, either drawn or written, often mirrored the images used by the British pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
151
0
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(170 citation statements)
references
References 36 publications
5
151
0
14
Order By: Relevance
“…Furthermore, it is necessary to "properly acknowledge the news media as the primary intermediary between science, politics, and the citizens, as well as their agenda-setting role for citizens' meaning making on climate change" (Olausson, 2011). Yet, both the media and individuals function as co-constructors of social representations (Breakwell, 2001), and there is an important and dynamic interplay between media representation, identity and personal experience (Smith & Joffe, 2013).…”
Section: Constructors Of Social Representationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, it is necessary to "properly acknowledge the news media as the primary intermediary between science, politics, and the citizens, as well as their agenda-setting role for citizens' meaning making on climate change" (Olausson, 2011). Yet, both the media and individuals function as co-constructors of social representations (Breakwell, 2001), and there is an important and dynamic interplay between media representation, identity and personal experience (Smith & Joffe, 2013).…”
Section: Constructors Of Social Representationsmentioning
confidence: 99%
“…Anchoring reflects the categorisation of unfamiliar objects through their comparison with an existing stock of familiar and culturally accessible objects. Recent empirical studies have demonstrated a widespread tendency for individuals to anchor climate change to ozone depletion, which constitutes the basis of their understanding of climate change, especially in the UK context (Lorenzoni et al, 2006;Smith & Joffe, 2013. This highlights the importance of a culturally sensitive, relativist epistemological approach to representations of climate change.…”
Section: Processes Of Social Representational Formationmentioning
confidence: 99%
See 3 more Smart Citations